Contrast enhancement for ultrasound-guided interventions: when to use it and what to expect? - Zeno Sparchez; Tudor Mocan; Rares Craciun; Mihaela Sparchez; Christian Nolsøe (Ultrasonography, 2022)
The use of contrast-enhanced ultrasonography (CEUS) has recently become synonymous with high-standard ultrasonography (US). From expanding the reach of US diagnostics to improving the precision of various invasive procedures, CEUS is rapidly becoming a standard in numerous niches. However, proficiency in CEUS comes with a cost, both from a learning curve and material standpoint, and as every growing field, lacks firm evidence and standardization. Therefore, in the current paper, we aim to provide an evidence-based review of available methods and to discuss the advantages and pitfalls of CEUS in interventional procedures, trying to provide strong evidence whenever available, or at least an educated expert opinion if data are lacking.